Hypocrisy and the politics of politeness: Manners and morals from Locke to Austen - Davidson, Jenny (Cambridge University, 2013)
In Hypocrisy and the Politics of Politeness, Jenny Davidson considers the arguments that define hypocrisy as a moral and political virtue in its own right. She shows that these were arguments that thrived in the medium of eighteenth-century Britain's culture of politeness. In the debate about the balance between truthfulness and politeness, Davidson argues that eighteenth-century writers from Locke to Austen come down firmly on the side of politeness. This is the case even when it is associated with dissimulation or hypocrisy. These writers argue that the open profession of vice is far more dangerous for society than even the most glaring discrepancies between what people say in public and what they do in private. This book explores what happens when controversial arguments in favor of hypocrisy enter the mainstream, making it increasingly hard to tell the difference between hypocrisy and more obviously attractive qualities like modesty, self-control and tact.